Grace for President - Kelly DiPucchio (New York, NY, United States Marvel Comics, 2012)
"Where are the girls?" When Grace's teacher reveals that the United States has never had a female president, Grace decides to be the first. And she immediately starts off her political career as a candidate the school's mock election! Author Kelly DiPucchio not only gives readers a fun introduction to the American electoral system, but also teaches them the value of hard work, courage, and independent thought--and offers an inspiring example of how to choose our leaders
Keywords: PY-UOI - How we Organize Ourselves; Government